EFEKTIVITAS STRATEGI READ ALOUD DALAM MENGENALKAN BAHASA INGGRIS PADA ANAK USIA DINI - Siti Marli’ah; Firdausi Nuzula Apriliyana (JCE (Journal of Childhood Education), 2021)
In order to face the global era, the ability to speak foreign languages, in this case English, is very important. So that the introduction of English should be pursued from an early age. However, the lack of knowledge of teachers and parents regarding strategies to introduce English to children has an impact on the lack of English language skills of children, therefore it is necessary to seek effective ways so that children's English language skills develop optimally during their best development period. The aim of this study is to determine the effectiveness of the strategy. Read Aload in introducing English to children. The research approach is a quantitative experiment with a pretest-posttest control group design through data collection techniques, observation and documentation, and analysis of hypothesis testing using the t test. The t test result in the control group was -17.245 while in the experimental group -5.844. There is a significant difference between language learning using the Read Aload strategy and others, proving that this strategy is effective for use in the introduction of English to children.